Kajian Pengaruh Konfigurasi Krib Terhadap Pola Arus Di Belokan - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian UGM, 2002)
ABSTRAK Current pattern control along channel bend can be done technically by proper lay-out of groyne at the channel banks with certain configuration. To get the optimal configuration of the groyne, current patterns downstream of the groyne with different lay-outs were analyzed quantitatively and qualitatively, Observation and evaluation of the effect of groyne lay-out to the current pattern along the channel bend was conducted by two approach, i,eâ physical modeling and mathematical modeling. Numerical simulation and physical model runs were conducted in a generic channel. Observation of hydraulic characteristics of flow at laboratory was done by particle image velocimetry method. Current pattern simulation was done with the BOSS SMS - FESWMS software module. This module is a 2-D depth average mathematical model. To get accurate simulation, the RMS of deviation of the numerical result from the measurement result at several locations was used as the indicator parameter in the calibration and the verification process. Quantity analysis of current pattern as hydraulic respons of the existence of the groyne was based on velocity distribution skewness at selected cross sections. The results showed that the variation of groyne length projection (17B=0,087-0,260) gave the change of the sk value by 31,4 - 325,8%, the variation of groyne setting direction (a/180=0,33-.0,67) gave the change of the sk value by 0,5 47,7%, and the channel's Reynolds number (Rech.7,97x104-1,51x105) gave the change of the sk value by 0,2 - 12,0%. The perpendicular groyne lay-out to the bank gave the strongest effect to change of velocity was compared with the other configuration (in comparison with the channel without groyne), whether change of velocity at downstream cross section at inner bend side (10,95 - 53,88%) or at upstream cross section at outer bend side (-13,12 - -51,77%).